The role of lifestyle in moderating the effect of quality and features on iphone purchasing decisions in Makassar city - Wahidah Abdullah; Putri Nurazizah Ramadhan M.Y; Alim Syariati (Institute of Computer Science (IOCS), 2023)
This research aims to determine the effect of product quality on purchasing decisions, the effect of product features on purchasing decisions, the effect of product quality on purchasing decisions which are moderated by lifestyle and the effect of product features on purchasing decisions which are moderated by lifestyle. This research is quantitative research using the partial least squares (PLS) method, using Smart PLS 3.3 software. The number of respondents in this study was 100 iPhone user respondents in the city of Makassar. The results of this research show that quality has a positive and significant effect on the decision to purchase iPhone smartphone products, features have a positive and significant effect on the decision to purchase iPhone smartphone products, lifestyle is not able to moderate the relationship between quality and the decision to purchase iPhone smartphone products, lifestyle is able to moderate the relationship between features on purchasing decisions for iPhone smartphone products.